EDUCATIONAL RESEARCH Competencies for Analysis and Applications - Mills, Geoffrey E.; Gay, L. R. (Pearson, 2019)
Educational Research is a comprehensive, accessible introduction to educational research. The text uses engaging, straightforward language to introduce you to the information and skills required to successfully conduct research and to competently evaluate research. Long known for clear and at times humorous writing, the authors are accessible and thoughtful guides for readers who are being introduced for the 1st time to a field that many of them might find initially intimidating. The text provides a total instructional system that lays out clear learning targets and then supports you as you practice and develop expertise in both doing and reading research. The 12th Edition includes a new, separate chapter on ethics, expands its coverage of single-subject research, covers the latest digital strategies and tools for doing research and introduces you to the open-source statistics software R.